Selective axillary dissection in cancer of breast: sentinel node technique - Aizen, Bernardo; Simonet, Fernando; Lago, Fernando; Ardao, Gonzalo; Alonso, Oscar; Díaz, Gabriela; Gualco, Gabriela; Horvath, Jorge; Viera, Richard; Rodríguez, Robinson; et al. (Cirugía del Uruguay, 2003)
The paper reports initial experience with the technique involving identification of sentinel lymph node in selective management of axilla in patients suffering from breast cancer. Identification rate (95 % ) and predictive accuracy value (95 % ) validates efficiency of procedure as adequate for prediction of Axillary status in breast carcinoma.